Observation of direct CP violation in the measurement of the Cabibbo-Kobayashi-Maskawa angle γ with B± → D(*)K(*)± decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We report the determination of the Cabibbo-Kobayashi-Maskawa CP-violating angle γ through the combination of various measurements involving B±→DK±, B±→D∗K±, and B±→DK*± decays performed by the BABAR experiment at the PEP-II e+e− collider at SLAC National Accelerator Laboratory. Using up to 474 million B¯¯¯B pairs, we obtain γ=(69+17−16)° modulo 180°. The total uncertainty is dominated by the statistical component, with the experimental and amplitude-model systematic uncertainties amounting to ±4°. The corresponding two-standard-deviation region is 41°<γ<102°. This result is inconsistent with γ=0 with a significance of 5.9 standard deviations.
Im Titel sind "±", "Sternchen" und "Klammer" hochgestellt
Gesehen am 10.11.2021